MENINGKATKAN MINAT BERWIRAUSAHA MAHASISWA DI JAWA TIMUR - wati, Tego; Palupi, Dian; Rochdianingrum, Widhi Ariestianti (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
: Entrepreneurship is one of the college efforts  to increase its graduates’ competency as well as to reduce unemployment of college graduates. Therefore, entrepreneurship in academics should be developed because it gives greater contribution to the improvement of a nation. This research aimed to analyze students’ interest of entrepreneurship in East Java. The population of this research were students in East Java (STIESIA Surabaya, UNISLA Lamongan, Muhammadiyah University Malang, and Muhammadiyah University Gresik). The number of samples were 145 respondents; and the sampling technique used accidental sampling. The data analysis technique applied Structural Equation Modeling (SEM) models.  Therefore, this research found three results. First, there was no effect on the factor of socio demography consisting of gender, age, field study, parents occupied and experience on entrepreneurship. Moreover, the output result of the coefficient parameter found that the correlation among construct of socio demographic factor to the entrepreneurship interest showed insignificant on 0,001 (p=0,011) with standardized of coefficient parameter was -0,205. Second, there was an effect of personal factor to the entrepreneurship interest. The output of coefficient parameter indicated that correlation construct of personal factor to the entrepreneurship interest was significant on p=0,001 (sign of p=***) with standardized coefficient parameter was  0,616. Third, there was an effect on contextual factor which consists of entrepreneurship education, academic support, social support and environmental support to the entrepreneurship interest. Based on the result of coefficient parameter output found that the correlation of contextual factor construct to the entrepreneurship interest was significant on 0.001 (sign of p=***) with standardized of coefficient parameter was 0.389.